SPOT SURVEY PENINGKATAN KASUS MALARIA DI DESA WONOHARJO WILAYAH PUSKESMAS ROWOKELE KABUPATEN KEBUMEN - Dyah Widiastuti; Anggun Paramita Djati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2012)
Introduction : There was an increasing malaria cases on August 2011 in Wonoharjo village, Banyumas regency. 12 malaria cases were reported by Local Health Office. The aim of this study was to investigate the prevalence rate and the entomological situation in transmission area. Methods : Mass blood survey for microscopic diagnosis was conducted at Dukuh Beji and Lokarsa in Wonoharjo village on 13-15 August 2011. Entomological survey using landing collection method and light traps was conducted only at Dukuh Lokarsa in Wonoharjo village on 15-16 August 2011. Results : A total of 7 samples among 68 were positive by microscopy, giving a point prevalence of 10.3%. The species distribution was 57.1% trophozoit Plasmodium falciparum (Pfr), 28,6% trophozoit and gametosit P.falciparum (Pfrg) and 14.3% falciparum-vivax mixed infection. Increasing malaria cases was caused by imported cases in Wagirpadan village which located next to Wonoharjo village. The suspected mosquito vectors were An.balabacensis and An. maculatus which caught from indoor and outdoor resting collection. Conclussions : Indigenous malaria transmission occured in Wonoharjo with the suspected vector were An.balabacensis and An.maculatus. The peak of mosquito bitting time was on 20.00 – 21.00 WIB. Migration surveillance need to be done effectively.